CO2 Emissions and Environmental Implications in Nigeria - Ogundipe, Adeyemi A.; Okwara, Chiamaka; Ogundipe, Oluwatomisin M. (International Journal of Energy Economics and Policy, 2020)
Since the discovery of oil in 1956, the Nigerian economy has been dependent on fossil fuel as a means of energy generation, hence causing excessive emission of carbon dioxide in the environment. Given this background, this study investigates the effect of fossil fuel consumption on environmental quality in Nigeria. The study used secondary data from 1970- 2017 obtained from World Development Index (WDI) and employs the Johansen co-integration analysis. The result reveals that about 80% of carbon emissions in Nigeria are directly consequence of fossil fuel combustion. Also, within the period observed, pollution was found to be a rising function of income and pollution rises as communities becomes more densely populated. The study recommends an urgent design of sustainable energy framework and national sensitization on the multidimensional adverse consequences of the use of dirty fuels. Keywords: CO2 emissions, Fossil fuel, Environment, Climate Change JEL Classifications: Q53, L71, P28, Q54 DOI: https://doi.org/10.32479/ijeep.8050